Variance of IQ is partially dependent on deletion type among 1, 427 22q11.2 deletion syndrome subjects. Issue 10 (5th October 2018) - Zhao, Yingjie; Guo, Tingwei; Fiksinski, Ania; Breetvelt, Elemi; McDonald‐McGinn, Donna M.; Crowley, Terrence B.; Diacou, Alexander; Schneider, Maude; Eliez, Stephan; Swillen, Ann; Breckpot, Jeroen; Vermeesch, Joris; et al.
Abstract : The 22q11.2 deletion syndrome is caused by non‐allelic homologous recombination events during meiosis between low copy repeats (LCR22) termed A, B, C, and D. Most patients have a typical LCR22A‐D (AD) deletion of 3 million base pairs (Mb). In this report, we evaluated IQ scores in 1, 478 subjects with 22q11.2DS. The mean of full scale IQ, verbal IQ, and performance IQ scores in our cohort were 72.41 (standard deviation‐ SD of 13.72), 75.91( SD of 14.46), and 73.01( SD of 13.71), respectively. To investigate whether IQ scores are associated with deletion size, we examined individuals with the 3 Mb, AD ( n = 1, 353) and nested 1.5 Mb, AB ( n = 74) deletions, since they comprised the largest subgroups. We found that full scale IQ was decreased by 6.25 points ( p = .002), verbal IQ was decreased by 8.17 points ( p = .0002) and performance IQ was decreased by 4.03 points ( p = .028) in subjects with the AD versus AB deletion. Thus, individuals with the smaller, 1.5 Mb AB deletion have modestly higher IQ scores than those with the larger, 3 Mb AD deletion. Overall, the deletion of genes in the AB region largely explains the observed low IQ in the 22q11.2DS population. However, our results also indicate that haploinsufficiency of genes in the LCR22B‐D region (BD) exert an additional negative impact on IQ. Furthermore, we did not find evidence of a confounding effect of severe congenital heart disease on IQ scores in our cohort.